The strength and conditioning practices and perspectives of soccer coaches and players. Issue 4 (August 2022) - Weldon, Anthony; Wong, Sing T; Mateus, Nuno; Duncan, Michael J; Clarke, Neil D; Pears, Matthew; Owen, Adam L; Bishop, Chris
Strength and conditioning (S&C) is implemented across various sports and levels, but there is limited understanding of the personnel responsible for this, including their S&C practices and perspectives. Whereas recent evidence has shown that coaches and players are often tasked with the responsibility. Therefore, this study aimed to investigate: 1) the personnel responsible for delivering S&C across different levels of soccer, 2) the practices and perspectives of soccer coaches and players, and 3) to ascertain whether the practices employed align with contemporary evidence and guidelines. Forty-two soccer coaches and 30 soccer players completed an online survey with six sections: (a) informed consent, (b) background information, (c) education, qualifications, and prescription, (d) views on S&C, (e) exercise selection and preferences, and (f) issues and improvements. Frequency analysis was used to report responses to fixed-response questions and thematic analysis for open-ended questions. Most respondents reported S&C to be 'important' to 'very important' for all soccer, physical fitness, and injury parameters, with perspectives being predominantly aligned with S&C guidelines and research in soccer. Although S&C coaches were mostly responsible for delivering S&C sessions, over 60% of respondents disclosed S&C sessions were delivered independently or by support staff. This is problematic given only four coaches held S&C qualifications, and issues and improvements were mostly regarding a lack of S&C expertise and education. This study provides valuable information for S&C and soccer organizations. Particularly regarding the additional support required to ensure those responsible for delivering S&C in soccer have the appropriate knowledge and qualifications.